Régionalisation et mondialisation - Erich Fisbach (Caravelle)
Born at the beginning of the 20th century and focusing on realism, denunciation, the heterogeneity of spaces and social realities, the Bolivian novel adopts a regionalist point of view and traditional narrative techniques. Since the 90’s, the regional balances have been modified. Bolivia is now an urban country and the sudden burst of Internet has contributed to globalizing the country’s literature, the outlines of which will be analyzed through a few recent novels.